Thermal Analysis of NiAl30 Powder Mixture - Skolakova, Andrea; Salvetr, Pavel; Novak, Pavel (Manufacturing Technology Journal, 2018)
NiAl alloys belong to the group of modern materials for high temperature application due to their low density, excellent thermal stability and oxidation resistance. They could be used as high temperature components which are usually made of nickel superalloys, heat-resistant steel or even cobalt superalloys. Production of these alloys is relatively simple and moreover, they could be used at higher temperatures exceeding 1000 °C. However, their high melting points and poor casting properties complicate the production by melt-metallurgy process. Powder metallurgy and reactive sintering were found to be a suitable replacement for melt-metallurgy. Many phases form during reactive sintering and reaction conditions of their formation are not known or are contradictory. In this work, thermal analysis of NiAl30 (in wt. %) powder mixture was studied. Results offer the effect of heating rate on reaction temperatures, microstructure and phase composition.
Keywords: thermal analysis; NiAl system; reactive sintering; phase composition